The Price of Empowerment Experimental Evidence on Land Titling in Tanzania - Ali, Daniel Ayalew (The World Bank, 2014)
This paper reports on a randomized field experiment that uses price incentives to address economic and gender inequality in land tenure formalization. During the 1990s and 2000s, nearly two dozen African countries proposed de jure land reforms extending access to formal, freehold land tenure to millions of poor households. Many of these reforms stalled. Titled land remains the de facto preserve of wealthy households and, within households, men. Beginning in 2010, the study tested whether price instruments alone can generate greater inclusion by offering formal titles to residents of a low-income, unplanned settlement in Dar es Salaam at a range of subsidized prices, as well as additional price incentives to include women as owners or co-owners of household land. Estimated price elasticities of demand confirm that prices-rather than other implementation failures or features of the titling regime-are a key obstacle to broader inclusion in the land registry, and that some degree of pro-poor price discrimination is justified even from a narrow budgetary perspective. In terms of gender inequality, the study finds that even small price incentives for female co-titling achieve almost complete gender parity in land ownership with no reduction in demand